PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING DI SERTAI MODUL HASIL PENELITIAN PADA SUB POKOK BAHASAN METODOLOGI ILMIAH TERHADAP HASIL BELAJAR SISWA KELAS X SMA N 2 SUKOHARJO TAHUN PELAJARAN 2011/2012 - Dewi, Rina Kartika; Muzayyinah, Muzayyinah; Maridi, Maridi (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT - This research aims to find out the effect of the implementation Active Knowledge Sharing learning strategy with module of the research on review of sub scientific methodology learning achievement of the class X at SMA Negeri 2 Sukoharjo. This study is a quasi-experimental studies which use Posstest Only Control Group Design. The independent variable in this research is the application of cooperative learning, the Active Knowledge Sharing where as the dependent variable is students? achievement in learning biology at 3 levels?. Namely, cognitive, affective and psychomotor. The population of the study is the entire of class X at SMA Negeri 2 Sukoharjo in academic year 2011/2012. The samples is taken upon control group and treatment group. The sample is taken by using Cluster Random Sampling method. The data are collected by using test (for cognitive achievement) where as for the affective and psychomotor aspects the data are taken by using observation methods. The obtained data that is analyzed by using t-test.The result shows the implementation of Active Knowledge Sharinglearning strategy with module of the research on review of sub scientific methodology has taken good effect towards students? achievement in affective and psychomotor aspects, but has not on the cognitive achievement students in class X of Surakarta SMA Negeri 2 Sukoharjo. Keywords: Active Knowledge Sharing Learning Strategy, Learning Achievement.